Hubungan Pengetahuan Orang Tua Tentang Toilet Training Dengan Keberhasilan Dalam Penerapannya Pada Anak Pra Sekolah Di TK Anugrah Harapan Bangsa 2023 - Elpriska Elpriska (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Toilet training is a way to train children aged 1-3 years in controlling defecation and urination activities properly and correctly. According to the 2019 National Household Health Survey (SKRT), it is estimated that the number of toddlers who have difficulty controlling defecation and urination (bedwetting) at the age of up to pre-school reaches 75 million children. This phenomenon is triggered by many things, such as parents' lack of knowledge about how to train defecation and toileting, the use of compresses and many others (Riblat, 2017). The introduction and implementation of toilet training in children is very important. Knowledge is one of the factors that can influence the success of toilet training implementation. This study aims to determine the relationship between parental knowledge about toilet training, with the success in its application in pre-school children in kindergarten. Anugrah Harapan Bangsa Marelan in 2023, using the type of correlation descriptive research. The population and sample in this study were all parents who had pre-school age children as many as 130 people. This study used a total sampling method, instrument in the form of a knowledge questionnaire and the successful implementation of toilet training. The results of this study were tested using the chi-square test, the results obtained p value = 0.000 (<0.05) indicates that parental knowledge has a relationship with the successful implementation of toilet training in children. From the results of the study it can be concluded that the better the parents' knowledge, the better the results of the implementation of toilet training. For this reason, it is recommended that parents maintain and improve their knowledge about toilet training so that they can provide good and correct toilet training implementation results for their children. This can be done for example by attending health education counseling events, especially in the field of toilet training.